L. Bruce Laingen correspondence - Laingen, L. Bruce
Photocopies of two ALsS (1980 April 19 and July 7; Tehran) from Laingen while a hostage in Iran, written to Joel Hettger concerning the condition of the hostages, the Iran Hostage Crisis, relations between Iran and the U.S., and the political situation in Iran and the U.S.
Positive photocopies.
Diplomat. Full name: Lowell Bruce Laingen. Born 1922.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Hettger, Joel -- Correspondence; Iran Hostage Crisis, 1979-1981.; Hostages -- Iran; Hostages -- United States; Iran -- Foreign relations -- United States; Iran -- Politics and government -- 1979-; Diplomats